Two-Step Flow Amidation of Natural Phenolic Acids as Antiradical and Antimicrobial Agents - Pecora, Desirée; Magni, Anna M.; Vicinanza, Sara; Annunziata, Francesca; Princiotto, Salvatore; Donzella, Silvia; Meroni, Gabriele; Martino, Piera A.; Basilico, Nicoletta; Parapini, Silvia; Conti, Paola; Borsari, Chiara; et al. (Journal of Natural Products, 2025)
Natural hydroxycinnamic acid amides (HCAAs) and riparins offer significant health benefits. However, their extraction from natural sources is difficult, and traditional synthetic methods remain wasteful, raising the need for more efficient alternatives. In this work, a two-step chemo-enzymatic flow method for the efficient esterification and amidation of phenolic acids was developed and successfully applied to the synthesis of riparin derivatives and HCAAs. The flow Fischer esterification was optimized using vanillic acid as a model starting material and SiliaBond Tosic Acid (SCX-3) as an immobilized acid catalyst, achieving a quantitative yield in a short residence time. The following amidation step, catalyzed by immobilized Candida antarctica lipase B, was optimized in toluene, leading to the desired amides. The synthesized compounds were evaluated for their radical scavenging, antibacterial, and antileishmanial properties. Overall, this work disclosed a novel approach for the efficient synthesis of riparin derivatives and HCAAs with interesting biological properties.